2010
DOI: 10.1172/jci42297
|View full text |Cite
|
Sign up to set email alerts
|

Human keratinocytes are efficiently immortalized by a Rho kinase inhibitor

Abstract: Primary human keratinocytes are useful for studying the pathogenesis of many different diseases of the cutaneous and mucosal epithelia. In addition, they can form organotypic tissue equivalents in culture that can be used as epidermal autografts for wound repair as well as for the delivery of gene therapy. However, primary keratinocytes have a finite lifespan in culture that limits their proliferative capacity and clinical use. Here, we report that treatment of primary keratinocytes (originating from 3 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
314
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(351 citation statements)
references
References 41 publications
24
314
6
Order By: Relevance
“…The addition of a ROCK inhibitor rescued the migratory phenotype of Irf6-deficient keratinocytes, thus providing further evidence that the extensive fibers in mutant cells contribute to their slower migration, as reported previously (Arthur and Burridge, 2001). In separate studies, the addition of the same ROCK inhibitor led to the immortalization of human keratinocytes and increased proliferation (Chapman et al, 2010;McMullan et al, 2003), but this effect was dependent on coculture with human fibroblasts (Chapman et al, 2010). Our culture system does not contain fibroblasts, and the number of cells dividing during the scratch assay was not significantly different between the two groups (data not shown), suggesting that proliferation is unlikely to contribute to the rescued migratory phenotype.…”
Section: Discussionsupporting
confidence: 80%
“…The addition of a ROCK inhibitor rescued the migratory phenotype of Irf6-deficient keratinocytes, thus providing further evidence that the extensive fibers in mutant cells contribute to their slower migration, as reported previously (Arthur and Burridge, 2001). In separate studies, the addition of the same ROCK inhibitor led to the immortalization of human keratinocytes and increased proliferation (Chapman et al, 2010;McMullan et al, 2003), but this effect was dependent on coculture with human fibroblasts (Chapman et al, 2010). Our culture system does not contain fibroblasts, and the number of cells dividing during the scratch assay was not significantly different between the two groups (data not shown), suggesting that proliferation is unlikely to contribute to the rescued migratory phenotype.…”
Section: Discussionsupporting
confidence: 80%
“…Progress in normal epithelial biology has shown that the addition of a RHOā€associated protein kinase (ROCK) inhibitor1, 2 to traditional keratinocyte growth medium and mitotically inactivated 3T3ā€J2 murine embryonic feeder cell coā€culture3 can increase the number of cells expanded in vitro and help to initiate cultures from small samples. Traditionally, the primary culture of human cancer cells has been challenging, with few tumors amenable to culture on plastic, so this protocol, known as ā€œconditional reprogrammingā€ or ā€œ3T3ā€‰+ā€‰Y,ā€ has naturally attracted attention in the cancer community.…”
Section: Introductionmentioning
confidence: 99%
“…Coculture of keratinocytes with irradiated 3T3 feeder cells in the presence of the RhoA kinase inhibitor Y-27632 (Y) massively expands the cell number (6).…”
mentioning
confidence: 99%